Karsinoma Sel Basoskuamosa Palpebra Rekuren: Laporan Kasus - Supit, Wenny (Medical Scope Journal, 2021)
Abstract: Basosquamous carcinoma (BSCC) is a rare type of skin cancer with an incidence of less than 2% of all skin cancers and the risk of local recurrence ranges between 15% and 50%. We reported a male, aged 57 years old, working as a civil employee, came to the eye clinic with a recurrent BSCC in the right lower palpebral since a month ago. The patient was previously diagnosed as BSCC and had undergone a surgery to remove cancer cells in 2017. However, in 2019, a scan of the axial incision of the head revealed a tumor mass in the right infraorbital area with T4N0Mx. The hypodense structured tumor mass showed increased contrasting. The opera-tive management performed was extensive excision and deep excision with rotational flaps and drainage attached. Histopathological examination of the tumor tissue and excision margins, optic nerve tissue, as well as infraorbital bone tissue indicated a BSCC. Diagnosis of BSCC was confirmed based on anamnesis, physical examination, ophthalmic examination, head CT scan with contrast, and histopathological examination. This case report was aimed to explore BSCC especially in palpebra due to the lack of data of similar cases as well as the potential for diagnosis and promising management.Keywords: basosquamous carcinoma (BSCC), palpebral, reccurentÂ Â Abstrak: Karsinoma basoskuamosa (BSCC) merupakan jenis kanker kulit yang langka dengan kejadian kurang dari 2% dari semua jenis kanker kulit namun dengan risiko kekambuhan lokal berkisar 15% dan 50%. Kami melaporkan kasus seorang laki-laki berusia 57 tahun, bekerja sebagai ASN, datang ke klinik mata dengan BSCC palpebra kanan bawah berulang sejak satu bulan lalu. Pasien sebelumnya didiagnosis dengan BSCC dan telah menjalani operasi untuk mengangkat sel kanker pada tahun 2017. Namun, pada tahun 2019, pemindaian kepala sayatan aksial menunjukkan adanya massa tumor di area infraorbital kanan dengan T4N0Mx. Massa tumor berstruktur hipodens dengan kontras yang meningkat. Manajemen operatif dilakukan eksisi ekstensif dan eksisi dalam dengan flap rotasi dan drainase terpasang. Pemeriksaan histopatologik dilakukan terhadap jaringan tumor dan margin eksisi, jaringan saraf optik, serta jaringan tulang infraorbital dengan simpulan suatu BSCC. Pada kasus ini diagnosis BSCC ditegakkan berdasarkan anamnesis, pemeriksaan fisik, pemeriksaan oftalmologi, pemeriksaan penunjang berupa CT scan kepala dengan kontras, dan pemeriksaan histopatologik. Laporan kasus ini bertujuan untuk mendalami BSCC khususnya di palpebra karena minimnya data mengenai kasus yang serupa, serta potensi diagnosis dan penatalaksanaan yang menjanjikannya.Kata kunci: karsinoma basoskuamosa (BSCC), palpebra, rekuren